(NaNTI^NA L)QÆTERATURA (B:s)E (NDOW)QÆDNIK (B/s)E - (NbURKAT(B, (No(B. (Np(B.s; (Nb)QÃLQÃW(B, (Nr(B. (Ns(B.s)E; (NwI[NEWSXKA(B, (Nn(B. (No(B.s; (NsEM^INSXKIJ(B, (Ns(B. (Nw(B.,s; (NpONAMOR)QÆW(B, (No(B. (Nd(B.,s)E ((NkI)QÇW (B:s)E (NlIB)QÆDX(B,s)E, 1993)
(NdOW)QÆDNIK MÆSTITX BAGATOGRANNU ÆNFORMACÆ@ PRO PISXMENNIKÆW ANTI^NOSTÆ(B, Ç(NHN@ TWOR^U SPAD]INU(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NaNTI^NA L)QÆTERATURAs)E; (NsTARODAWN)QÆJ SWÆTs)E; (NANTI^NA M)QÆFOLOGÆQs)E; (NPISXMENNIKI ANTI^NOST)QÆs)E